Evaluation of Partnership Working in Cities in Phase IV of the WHO Healthy Cities Network - Lipp, Alistair (Springer US, 2012)
An intersectoral partnership for health improvement is a requirement of the WHO European Healthy Cities Network of municipalities. A review was undertaken in 59 cities based on responses to a structured questionnaire covering phase IV of the network (2003–2008). Cities usually combined formal and informal working partnerships in a pattern seen in previous phases. However, these encompassed more sectors than previously and achieved greater degrees of collaborative planning and implementation. Additional WHO technical support and networking in phase IV significantly enhanced collaboration with the urban planning sector. Critical success factors were high-level political commitment and a well-organized Healthy City office. Partnerships remain a successful component of Healthy City working. The core principles, purpose and intellectual rationale for intersectoral partnerships remain valid and fit for purpose. This applied to long-established phase III cities as well as newcomers to phase IV. The network, and in particular the WHO brand, is well regarded and encourages political and organizational engagement and is a source of support and technical expertise. A key challenge is to apply a more rigorous analytical framework and theory-informed approach to reviewing partnership and collaboration parameters.